Alternative Vaporized Gasoline Fuel: Development and Application of an Eco-friendly Carbon-free Gasoline Fuel (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Global warming , climate change effects are majorly due to increasing concentrations ofgreenhouse gases (GHGs) such as vehicle, IC engine emitted CO2 in the atmosphere. is a globalwarming. Recently more than 60 effective causes of CO2 emission are human activities. Currently inIndia sustainable development step towards less usage of fossil fuel utilization is in prime importance.An economical and environment friendly fuel has been derived by using Petrol, Kerosene and Water indefinite amount. The final gas product is the alternative carbon free gasoline (nearly octane) has pureblue flame. This fuel is total carbon free and providing very silent blue flame which indicates its purity.Possible flame temperature of gas is more than 2000˚C. Also its production cost is negligible and hasno byproducts at the time of manufacturing. For the testing purpose and application as fuel, it has beentasted on a Bunsen's burner which showed a 4 hours regular burning for 250 ml of all Petrol, Keroseneand Water respectively with very negligible knockings, smoke and CO2. This carbon free alternativegasoline fuel can be used in different engines, vehicles, generators, boilers, kitchen gas burner, etc.This will be the best option for industrial boilers as the fuel with very high flame temperature with itshigh efficiency parameters. This can be stored safely in storing tanks for longer time.